Confucius Institute as an instrument for the promotion of Chinese public and cultural diplomacy in Pakistan. - Muhammad Asif (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
To advance China's language and culture and improve China's foreign image, since 2004, China has constructed over 700 Confucius Classrooms and Institutes. Despite the vast number of Confucius Institutes, very little has been known about operating or what they accomplish inside institutions. Using a variety of media sources, including the government policy, newspaper reports from the internet, Confucius institutes themselves, individual blogs are written by Chinese language teachers, and the observations of university academics, it begins by discussing the concepts of cultural and public diplomacy, cultural associations as a conceptual framework for assessing Confucius Institutes. One of the most effective ways to change people's views of other countries and cultures is direct public diplomacy. In the community of national cultural institutions, the Confucius Institutes are a standout member because of their connection to China's development. China's foreign policy goals are now boosting the availability of Chinese language training across the world. Since 2013, the Belt and Road Initiative (BRI) has opened up a new avenue for Chinese language instruction abroad. They recognize that showing their cultural background is a way to illustrate who they are while also portraying a positive image, which enables them to accomplish their political aims. This article examines the relevance of the China-Pakistan Economic Corridor (CPEC) and its influence on Pakistani culture and language using the Pakistan Confucius Institutes as a case study. The study emphasizes the need for more vital bilateral collaboration between two nations to construct a community of cultural enterprises and linguistic centers that both countries can share. In Pakistan, the CPEC is causing a linguistic shift. Both nations' cultures may be openly shared. As a result, CPEC's efficacy as a language changer cannot be denied.